Detection of EBV, HBV, HCV, HIV-1, HTLV-I and -II, and SMRV in Human and Other Primate Cell Lines. (29th April 2010) - Uphoff, Cord C.; Denkmann, Sabine A.; Steube, Klaus G.; Drexler, Hans G.
Abstract : The high prevalence of contaminated cell cultures suggests that viral contaminations might be distributed among cultures. We investigated more than 460 primate cell lines for Epstein-Barr (EBV), hepatitis B (HBV), hepatitis C (HCV), human immunodeficiency virus type 1 (HIV-1), human T-cell leukemia/lymphoma virus I and II (HTLV-I/-II), and squirrel monkey retrovirus (SMRV) infections for risk assessment. None of the cell lines were infected with HCV, HIV-1, or HTLV-I/-II. However, one cell line displayed reverse transcriptase activity. Thirty-nine cell lines harbored EBV DNA sequences. Studies on the lytic phase of EBV revealed that five cell lines produce EBV particles and six further cell lines produced EBV upon stimulation. One cell line contained an integrated HBV genome fragment but showed no virus production. Six cell lines were SMRV-infected. Newly established cell lines should be tested for EBV infections to detect B-lymphoblastoid cell lines (B-LCL). B-LCLs established with EBV from cell line B95-8 should be tested for SMRV infections.